Melmoth : a novel - Perry, Sarah, 1979- (Custom House, 2018)
"It has been years since Helen Franklin left England. In Prague, working as a translator, she has found a home of sorts--or, at least, refuge. That changes when her friend Karel discovers a mysterious letter in the library, a strange confession and a curious warning that speaks of Melmoth the Witness, a dark legend found in obscure fairy tales and antique village lore. As such superstition has it, Melmoth travels through the ages, dooming those she persuades to join her to a damnation of timeless, itinerant solitude. To Helen it all seems the stuff of unenlightened fantasy. But, unaware, as she wanders the cobblestone streets Helen is being watched. And then Karel disappears. . . "--